Mapping corporate tax planning and corporate social responsibility: a hybrid method of category analysis - Araújo, Lurdes (2024)
The relationship between corporate tax planning (CTP) and corporate social responsibility (CSR) is complex, with various perspectives, and a detailed scientific analysis of this relationship is required. This complexity arises from the conflicting interests of maximizing shareholder value through tax strategies while meeting societal expectations of ethical behaviour and transparency. So, the main objective of this research is to reveal the state of the art regarding the relationship between these two concepts. To achieve this goal and map the scientific literature relating to CTP and CSR, the Scopus and Web of Science (WoS) databases were used, resulting in a screening process identifying 47 relevant articles. The methodology employed is hybrid, combining a systematic review and category analysis. The main results reveal a strong relationship between corporate tax planning and CSR. Tax avoidance is the focus, followed by tax aggressiveness due to the conflict between shareholder benefits and social obligations. In addition, the most tested theory is risk management. This study highlights the interdisciplinary nature of CTP and CSR research, integrating accounting, business ethics, and management for a holistic understanding of corporate behaviour. The focus on tax avoidance underscores its key role in the CTP-CSR relationship, reinforcing theories that link tax practices to corporate ethics and suggesting aggressive tax strategies can undermine CSR efforts. As the main practical implication, the study suggests that policymakers should promote transparency in companies’ tax practices and encourage CSR activities, aligning companies’ behaviour with society’s expectations and improving compliance with tax obligations.